1994
DOI: 10.1177/003072709402300306
|View full text |Cite
|
Sign up to set email alerts
|

Maize Productivity for the 21st Century: the African Challenge

Abstract: Maize is a major food crop in southern and eastern Africa. It is widely grown by smallholders, and forms an important part of the transformation of smallholder agricultural systems that has taken place this century. But, despite commendable efforts in technology development at both the national and the international level, agricultural productivity is well below that necessary to help create strong, healthy African economies. No single solution is likely to be found for this problem. In this paper, two major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
0
6
0
3
Order By: Relevance
“…Many researchers contend that basic problems of availability, for example "getting the right fertilizer to the right place at the right time", are at least as important as price-response Soil Fertility Management in Sub-Saharan Afrtica 38 interactions in determining fertilizer use (Fontaine 1991;Pinstrup-Andersen 1993;Blackie 1995). Though these are often referred to as non-price factors, distribution problems affect prices and are not separable from them.…”
Section: Unavrailability Of Techniques or Inputsmentioning
confidence: 99%
“…Many researchers contend that basic problems of availability, for example "getting the right fertilizer to the right place at the right time", are at least as important as price-response Soil Fertility Management in Sub-Saharan Afrtica 38 interactions in determining fertilizer use (Fontaine 1991;Pinstrup-Andersen 1993;Blackie 1995). Though these are often referred to as non-price factors, distribution problems affect prices and are not separable from them.…”
Section: Unavrailability Of Techniques or Inputsmentioning
confidence: 99%
“…Recent discussions with breeders, farmers and researchers indicated that stalk and cob rots are one of the major constraints on this staple food crop (Blackie, 1994;Nowell, 1994;O. CIMMYT, 1995, Jeffers personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Maize is one of the major staple food grains grown throughout both the developed and the developing world. In developing countries much is grown by small growers, for their own consumption and also in order to provide a modest source of income (Blackie, 1994;Julian et al 1995). Stalk and cob rots are still major constraints to production.…”
Section: Introductionmentioning
confidence: 99%
“…Economic growth in rural areas has been insufficient to offer alternative means of employment for the rural poor. Profits from farming at low levels of productivity have been too small to allow farmers to reinvest in their farms and maintain productivity at acceptable levels (Eicher, 1990;Blackie, 1994). Meanwhile, continual increases in population have depleted both the available resource base and social entitlements which hitherto provided a state of equilibrium in rural areas (Lele, 1989).…”
Section: International Consensus On Methodologies and Approachesmentioning
confidence: 99%